2017
DOI: 10.1177/0954410017748989
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of riblet effects on the aerodynamic performance and flow characteristics of a delta wing

Abstract: The present study investigates the effects of riblet on the aerodynamic performance and flow characteristics of a delta wing. Flow visualizations and measurements of the aerodynamic forces are performed on a smooth-surface as well as few textured-surface models of the delta wing. Flow visualizations were undertaken at flow speed of 2.5 m/s and various angles of attack in a vertical wind tunnel. The effects of riblet are investigated on the diameter of the vortices, location of the vortex breakdown, distance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…They stated that the flow control method by using an actuator causes significant changes in the strength, size, and shape of the leading-edge vortices. Saeedi Rizi et al 24 reported that riblets could control the vortical flow structure over the delta wings and enhance the aerodynamic performance of delta wings.…”
Section: Introductionmentioning
confidence: 99%
“…They stated that the flow control method by using an actuator causes significant changes in the strength, size, and shape of the leading-edge vortices. Saeedi Rizi et al 24 reported that riblets could control the vortical flow structure over the delta wings and enhance the aerodynamic performance of delta wings.…”
Section: Introductionmentioning
confidence: 99%